An Investigation into the leading factors that affect teachers' decision-making towards curricula change in Irish post-primary schools - Byrne, Christopher (Trinity College Dublin. School of Education. Discipline of Education, 2022)
In recent years there has been an international resurgence in curriculum change. Intercontinental influences such as globalisation and international testing have resulted in a transformation of traditional educational approaches. These influences have been the catalyst behind the trends towards developing students with the skills required for a rapidly developing workplace where the only certainty is our uncertainty of their future requirements. This coupled with the digital revolution has changed peoples perceptions of not only how we learn but how we access information and what significance we place on knowledge. These challenges have resulted in a renewed effort across developed countries to implement curricular change which places the student at the centre of the learning experience and focuses on them becoming adaptable problem solvers. To achieve these aims, modern curriculum development has tended to follow a trend towards the deregulation of conventional prescriptive curricula. This new flexibility afforded to schools is often guided by a national curriculum that focuses on the learning outcomes of the student as opposed to the content of the learning. This model allows teachers and schools to design and tailor a curriculum to the needs of their students while also affording curriculum development bodies and governments influence over the national curriculum. However, this has resulted in a substantial change in the practice of teachers, often resulting in trepidation and resistance. Such opposition threatened the enactment of the changes in all but name and in some countries resulted in industrial action. Lines were drawn with curriculum developers and governments on one side and teachers and their unions on the other; the ensuing struggle threatened the very fabric of education systems. iv This thesis examines the complex and interwoven reasons behind why some changes are resisted and others embraced by teachers. This study primarily focuses on the factors that affect teachers decision-making towards curricula change in Irish post-primary schools. The overall goal of uncovering these factors is to provide stakeholders in education with an overview of how teachers make decisions about change. The thesis begins with an introduction to curriculum change and details the aims of this project. The literature review in this study explores curriculum structure, models, development and implementation from a national and international perspective. It examines existing literature on international curriculum trends and culminates in an overview of curricula reform in Ireland. The study then proceeds to develop a conceptual framework to explore the factors that may affect the decision-making process of teachers when faced with curriculum change. In this chapter, the author hypothesises the concepts that he believes may influence teachers decision-making, drawing on the fields of psychology, economics, behavioural economics, sociology and organisational change. The methodological approach to data collection encompasses three different methods: a survey, interviews and a Delphi study. All of these findings were analysed to assess the prevalent factors influencing teachers decision-making about curriculum change. Based on these findings, the main factors were organised into an explanatory framework. This framework comprises of three stages: the precognitive stage, the cognitive stage and the adjustment stage. Each stage consists of several factors that influence decision-making about curriculum change. Understanding these factors that affect Irish post-primary teachers decision-making about the change process can play a progressive role in the design and implementation of future curriculum change. It will also help teachers understand how they themselves make decisions about change.
APPROVED
Keywords: Curriculum change, organisational change, decision making,